2007
DOI: 10.1002/anie.200603593
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Interconversions of Coordination Networks and Hydrogen‐Bonded Salts

Abstract: Thermal or chemical treatment of crystalline 4,4′‐bipyridinium salts of [MCl4]2− (M=Co, Zn, Fe, or Pt) leads to HCl loss and formation of coordination network solids [{MCl2(4,4′‐bipy)}n]. For M=Co, Zn, and Fe, these solids can also be prepared by mechanochemical means. Their exposure to HCl vapor or the mechanochemical reaction of metal dichlorides with [4,4′‐H2bipy]Cl2 gives [4,4′‐H2bipy]2+ salts of [CoCl4]2−, [ZnCl4]2−, and, for the first time, [FeCl4]2−.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
80
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(82 citation statements)
references
References 59 publications
2
80
0
Order By: Relevance
“…However, it has been shown that changes in the metal coordination environment might also be feasible in non-porous materials through the chemisorption of some molecular species 24 . A particular example of such a dramatic transformation involves the reaction of molecular solids with gaseous HX (X = Cl, Br) leading to profound structural changes 25,26 , where porosity is not necessary, as the chemisorption process involves the removal/addition of HX from/to the framework itself.…”
mentioning
confidence: 99%
“…However, it has been shown that changes in the metal coordination environment might also be feasible in non-porous materials through the chemisorption of some molecular species 24 . A particular example of such a dramatic transformation involves the reaction of molecular solids with gaseous HX (X = Cl, Br) leading to profound structural changes 25,26 , where porosity is not necessary, as the chemisorption process involves the removal/addition of HX from/to the framework itself.…”
mentioning
confidence: 99%
“…Structures 2phenCdBr, 5, 2phenHgBr, 8, and 2phenCd/HgBr, 11 (all bromo-ligand containing), exhibit q angles in the range 64.7 (8) to 67 (1) . The s values for cation 2 indicate that the iodo-ligand containing structures 3, 6 and 9 show the largest deviation of atom C(9) from the aromatic plane.…”
mentioning
confidence: 99%
“…As previously reported (27), the crystalline salts ½4;4 0 -H 2 bipy ½MCl 4 1 (M ¼ Co (1), Zn) can be prepared from treatment of the appropriate metal(II) chloride with ½4;4 0 -H 2 bipy 2þ in aqueous HCl solution. More generally, crystalline 1 (and the analogous zinc and iron salts) can be prepared in the solid state by grinding together stoichiometric amounts of MCl 2 and ½4;4 0 -H 2 bipy Cl 2 or by hydrochlorination of the coordination MOF solid ½fðμ-4;4 0 -bipyÞCoCl 2 g n 2 by HCl absorption.…”
Section: Resultsmentioning
confidence: 95%
“…We have also observed that these compounds can be used as precursors to the formation of metal-nitrogen coordination polymers by HCl elimination (27). Finally, we have explored the utility of other solid-state reactions to prepare metal chloride adducts of nitrogen bases such as 4,4′-bipyridine and imidazole (28).…”
mentioning
confidence: 99%